A single-component and hemi-hip prosthesis followed up for 43 years: A case report. Issue 8 (February 2019) - Liu, Yuan; Chen, Hang-jun; Zhang, Bin; Liu, Xu-Qiang; Xiao, Jun; Cheng, Cheng-Kung; Dai, Min
Abstract: Rationale: Giant cell tumor (GCT) is a locally aggressive bone tumor with a high recurrence rate if not completely excised. And reconstructive hip surgery using an artificial prosthesis in a young active patient is controversial because of problems related to the durability of the artificial joint. Patient concerns: A 30-year-old man presented with right hip pain and other more severe symptoms, but without fever or night sweats. After 4 months, he experienced intense pain at the root of the right leg and limitation of motion after falling from a bicycle. Diagnoses: Giant cell tumor. Interventions: The patient was treated with surgical resection of the total tumor, and hemiarthroplasty of the hip joint using a custom-made titanium femoral prosthesis. Outcomes: The patient could perform activities of daily living, even walking long distance without pain. He continued to work as a teacher for 30 years and retired 11 years after the surgery. Lessons: A well-designed, custom-fitted, single-component, wear-resistant joint prosthesis should be the brand-new direction of development of artificial joints.